Comparison of Physical Fitness of Turkish and Iraqi Sedentary Boys - Harun Genç; Karaemali Ghazwan; Gökmen Kılınçarslan (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to compare the anthropometric and physical fitness values of Turkish and Iraqi sedentary boys who were educated in 2017-2018 education year. A total of 68 boys, aged 13,60 + 0,60 with 35 Turkish and 13,81 + 0,84 with 33 Iraqi, who had no health problems and no disadvantages in entering the physical education course, participated voluntarily. Anthropometric measurements (age, height, weight, body mass index) of the boys participating in the study were taken. Eurofit Test Battery tests (flamingo balance test, sit-in flexibility test, standing long jump test, paw force test, shuttle test, twisted arm hanging test, disk touch test, 10 × 5 meter agility running test, and vo2 max shuttle running test). The arithmetic mean and standard deviation of all measurements are calculated. Statistical analyzes of the measurements were made in the SPSS 22 program. Regular measurement of physical fitness values, including the physical and anthropometric characteristics of secondary school children, can be used to monitor the physical fitness levels and to set national norms by arranging criteria related to the physical characteristics of students. In addition to this, it can also contribute to the healthy growth of children, to the efficient human power and to the selection of qualified athletes.